PENERAPAN ALGORITMA GAP ANALISIS UNTUK PENILAIAN KINERJA GURU BERBASIS WEB - Thomas Edyson Tarigan; Emy Susanti; Kristian Rio Vernando (LPPM STMIK El Rahma Yogyakarta, 2022)
Determining teachers who have achievements from a number of teachers will take a lot of time. Because it requires a series of assessments based on certain criteria. Based on the Regulation of the Minister of National Education Number 16 of 2007 concerning Academic Qualification Standards and Teacher Competencies, there are several criteria used to determine teacher competence, the criteria are grouped into 4 criteria, namely, Pedagogic, Personality, Social and Professional. The focus of this research is to utilize the gap analysis algorithm to determine the teacher with achievement using 4 criteria. These regulations are referred to as the realm of competence. As a case study to support this research data were taken from SDN 02 Menukung District, Melawi Regency, West Kalimantan Province. The result of this research is the teacher achievement ranking which is measured based on the above criteria. The results of the implementation of the implementation of the gap analysis algorithm show that the application of the gap analysis algorithm is able to provide alternative decisions for outstanding teachers with reference to the percentage weight values ​​for core and secondary factors and the percentage weighted values ​​for the competence domain have been determined